Fhl1, a new spatially specific protein, regulates vein graft neointimal hyperplasia - Chaoqun Wang; Jiantao Chen; Zicong Feng; Bohao Jian; Suiqing Huang; Kangni Feng; Haoliang Liu; Zhuoming Zhou; Ziyin Ye; Jing Lu; Mengya Liang; Zhongkai Wu (Clinical and Translational Medicine)
Abstract Background Vein grafts are commonly employed in revascularisation surgery for multivessel coronary artery disease, yet neointimal hyperplasia (NIH) remains a critical impediment to the long‐term patency of these grafts. Despite this, effective methods to precisely identify and target interventions for the neointima are still inadequate. Methods In this study, Sprague–Dawley (SD) rats were used to establish an external jugular vein transplantation model, and the NIH pathophysiological process was tracked across 11 time points (0–35 days) using various histological stains. Spatial transcriptomics was performed on normal veins and 19‐day grafts to explore gene expression in neointimal regions. Immunohistochemical analysis identified neointima‐specific markers, while NIH progression was assessed in SD rats with four and a half LIM domains protein 1 (Fhl1) knockout and in human saphenous veins (HSV) with adenovirus‐mediated Fhl1 overexpression. Results Typical neointimal formation commenced by day 11 postgrafting and peaked at day 19. Neointimal cells originated from newly generated α‐SMA(+) repair cells located outside the grafted vein, displaying a hybrid fibroblast‐smooth muscle cell phenotype. Spatial transcriptomics identified stable and sustained Fhl1 expression within the neointima throughout the entire NIH phase. Systemic knockout of Fhl1 in SD rats via the phosphoinositide 3‐kinase pathway exacerbated graft inflammation, heightened cell proliferation, and accelerated NIH. Conversely, FHL1 overexpression in cultured HSV suppressed NIH. Conclusion These findings indicate that, following grafting into the arterial system, the newly formed repair cells external to the grafted vein play a pivotal role in NIH, with neointimal cells exhibiting stable and continuous Fhl1 expression. Fhl1 serves as a protective factor against NIH both in vivo and in HSV, likely due to its anti‐inflammatory and anti‐proliferative effects. Key points This study firstly used spatial transcriptomics technique to analyse the neointima and generated a specific neointimal transcriptomic atlas. Fhl1 exhibits specific and stable expression in the spatial region of the neointima. It has thus far the highest enrichment of expression in the neointima in NIH phases, suggesting that it is a prominent molecular biomarker of neointima. We generated rats with a Fhl1 deletion and found that insufficient Fhl1 expression caused an increase in the severity of vascular inflammation and proliferation during neointimal hyperplasia. Adenovirus‐mediated FHL1 overexpression in human saphenous vein have beneficial effects in preventing neointimal hyperplasia. These highlight its potential as a therapeutic target for mitigating vein graft failure associated with cardiovascular procedures. Spatial transcriptomics profiles and morphological observations demonstrated that a newly generated cell population outside the grafted vein with hybrid phenotype between SMCs and fibroblasts contributes to neointimal formation.